Inovasi Strategi Pembelajaran Pendidikan Agama Islam Berbasis Kontekstual Sebagai Implementasi Kebijakan Kurikulum Merdeka - Maidah, Nurul; Nurhidayati, Titin (Journal of Islamic Education and Pedagogy, 2025)
This study aims to analyze the implementation of innovative contextual-based learning strategies in Islamic Religious Education (PAI) at Vocational High Schools (SMK), as well as their impact on strengthening students' religious character in support of the Merdeka Curriculum policy. The research approach used is qualitative with a phenomenological design, involving in-depth interviews with teachers and students as well as field observations. The results show that the application of contextual approaches in PAI learning, such as Project-Based Learning (PjBL) and Contextual Teaching and Learning (CTL), successfully creates more meaningful and relevant learning for students by linking the teaching materials to real-life contexts. Additionally, the differentiated approach applied by the teachers provides space for students to learn according to their individual learning styles and needs, thus enhancing active participation and deep understanding. The implementation of the Merdeka Curriculum, which grants teachers the autonomy to design more creative and adaptive learning, further strengthens the spiritual and moral competitiveness of SMK graduates. The findings of this study indicate that contextual-based learning strategies can improve students' religious character, as evidenced by an increase in religious activity, honesty, responsibility, and tolerance. Therefore, innovation in contextual-based PAI learning in SMKs significantly contributes to the development of students' character and readiness to face life challenges in the workplace and society.